Reproducibility: A Researcher-Centered Definition - Sebastian Stefan Feger; Paweł W. Woźniak (Multimodal Technologies and Interaction, 2022)
Recent years have introduced major shifts in scientific reporting and publishing. The scientific community, publishers, funding agencies, and the public expect research to adhere to principles of openness, reproducibility, replicability, and repeatability. However, studies have shown that scientists often have neither the right tools nor suitable support at their disposal to meet these modern science challenges. In fact, even the concrete expectations connected to these terms may be unclear and subject to field-specific, organizational, and personal interpretations. Based on a narrative literature review of work that defines characteristics of open science, reproducibility, replicability, and repeatability, as well as a review of recent work on researcher-centered requirements, we find that the bottom-up practices and needs of researchers contrast top-down expectations encoded in terms related to reproducibility and open science. We identify and define reproducibility as a central term that concerns the ease of access to scientific resources, as well as their completeness, to the degree required for efficiently and effectively interacting with scientific work. We hope that this characterization helps to create a mutual understanding across science stakeholders, in turn paving the way for suitable and stimulating environments, fit to address the challenges of modern science reporting and publishing.